Quality improvement through audit: Zuclopenthixol acetate prescribing, monitoring and patient outcomes in a regional health service. (February 2023) - Vellar, Kane; Khalid, Usman; Coleman, Mathew
Objective: Prescribers' expectations of Zuclopethixol Acetate's (ZA) efficacy and tolerability are shaped by clinical experience and organisational culture; however, these expectations may not be consistent with current evidence and best practice. Methods: Quality improvement project (QIP) through a process audit of ZA prescribing, monitoring and patient outcomes (adverse events) in order to identify issues requiring intervention to align with service standards and practices. Results: QIP interventions resulted in a statistically significant shift in psychiatrist oversight, identifying high dose ZA with adverse outcomes and cessation of prescribing/administration within the Emergency Department. Clinically significant changes in patterns of prescribing were observed between pre-post intervention audits. Conclusion: Entrenching an evidence-based QIP approach to clinical practice can effect clinically significant patterns of practice change to improve safe prescribing and drug monitoring.